Characteristics of patients with hypertension in a population with type 2 diabetes mellitus. Results from the Turkish Nationwide SurvEy of Glycemic and Other Metabolic Parameters of Patients with Diabetes Mellitus (TEMD Hypertension Study). Issue 2 (April 2021) - Sabuncu, Tevfik; Sonmez, Alper; Eren, Mehmet Ali; Sahin, Ibrahim; Çorapçioğlu, Demet; Üçler, Rıfkı; Akin, Şafak; Haymana, Cem; Demirci, İbrahim and Atmaca, Ayşegül and Ersöz, Halil Önder and Satman, Ilhan and Bayram, Fahri and , and Güldiken, Sibel and Aytürk, Semra and Yilmaz, Murat and Aşik, Mehmet and Dinççağ, Nevin and Satman, İlhan and Çakmak, Ramazan and Türker, Fulya and İdiz, Cemile and Hacişahinoğullari, Hülya and Bağdemir, Elif and Yildiz, Büşra and Yumuk, Volkan Demirhan and Haliloğlu, Özlem and Salman, Serpil and Sancak, Seda and Özsari, Levent and Çağiltay, Eylem and Deyneli, Oğuzhan and İmre, Eren and; n, Sait and; an, Şerife Nur and; ntaş, Yüksel and; et al.
Highlights: Hypertension often accompanies type 2 diabetes mellitus. Co-existence of hypertension increases the frequency of complications of diabetes mellitus. Although most patients receive treatment, only half of blood pressures are on the target. Masked hypertension is an another important issue in diabetic population. Abstract: Background: The present survey aimed to find out the demographical and clinical characteristics of patients with hypertension in a population with type 2 diabetes mellitus (T2DM) in Turkey. Methods: Patients with T2DM who were followed-up in tertiary endocrine units for at least last one year were recruited. Demographic, clinical and biochemical data of the patients were collected. Hypertension was defined as taking anti-hypertensive medications or having office arterial blood pressure (ABP) ≥140/90 mmHg or home ABP ≥ 130/80 mmHg. Results: A total of 4756 (58.9% women) diabetic patients were evaluated. The percentage of patients with hypertension was 67.5% (n = 3212). Although 87.4% (n = 2808) of hypertensive patients were under treatment, blood pressure was on target in 52.7% (n = 1479) of patients. Hypertension proportions were higher in woman (p = 0.001), older, more obese, and those who had longer diabetes duration, lower education levels, higher frequency of hypoglycemic events (all p < 0.001) and higher triglyceride levels (p = 0.003). LDL cholesterol level and the percentage of smokers were lower in hypertensive group than in non-hypertensive group (both p < 0.001). The percentage of macro and microvascular complications was higher in the hypertensive group than in the normotensive one (both p < 0.001). In multivariate logistic regression analysis, being a woman (OR: 1.26, 95% CI: 1.04–1.51, p = 0.016), smoking (OR: 1.38, 95% CI: 1.05–1.80, p = 0.020), regular physical activity (OR: 1.24, 95% CI: 1.01–1.53, p = 0.039) and the presence of macrovascular complications (OR: 1.38 95% CI: 1.15–1.65, p = 0.001) were the significant predictors of good ABP regulation. The ratios of masked and white coat hypertension were 41.2% and 5.7%, respectively. Conclusion: Our findings indicate that two-thirds (67.5%) of adult patients with T2DM have hypertension. Co-existence of hypertension increases the frequency of macro and microvascular diabetic complications in these patients. Despite the critical role of hypertension in morbidity and mortality, only half of the patients have favorable ABP levels. Masked hypertension seems to be another important issue in this population.